2023
DOI: 10.1111/hepr.13969
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the autoantibody assay in predicting the development of immune‐related adverse events in patients receiving atezolizumab plus bevacizumab combination therapy for unresectable hepatocellular carcinoma

Hitomi Takada,
Koji Yamashita,
Leona Osawa
et al.

Abstract: AimAtezolizumab plus bevacizumab (AB) combination therapy is the first‐line treatment for unresectable hepatocellular carcinoma (u‐HCC). The management of immune‐related adverse events (irAEs) is an important issue associated with achieving a good therapeutic response in patients receiving AB therapy. However, few studies have reported irAE development in patients receiving AB therapy. This study focused on the the association between irAE development and autoantibodies at baseline in patients receiving AB the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Autoantibodies are one of the most well-studied predictive biomarkers for irAEs. Several studies have shown that a pre-existing collection of autoantibodies such as antinuclear antibody, rheumatoid factor, or antithyroid antibodies (antithyroglobulin, and antithyroid peroxidase) before ICI treatment is associated with increased irAEs [ 11 , 12 , 13 , 14 ].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibodies are one of the most well-studied predictive biomarkers for irAEs. Several studies have shown that a pre-existing collection of autoantibodies such as antinuclear antibody, rheumatoid factor, or antithyroid antibodies (antithyroglobulin, and antithyroid peroxidase) before ICI treatment is associated with increased irAEs [ 11 , 12 , 13 , 14 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…However, the results were somewhat inconsistent when investigating which specific autoantibody was the main contributor to the association with irAEs. The most promising and well-studied autoantibody was anti-nuclear antibody [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], followed by rheumatoid factor [ 13 , 22 ], both studied in multiple types of solid tumors, including malignant melanoma and NSCLC. Some studies suggested a positive association between pre-existing autoantibodies and the development of any irAE [ 14 , 16 , 17 , 18 , 19 ], but some reported no association [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Currently, tumor markers, neutrophil to lymphocyte ratio, biomarkers, and imaging ndings are reported as factors that may predict overall responses. [4][5][6][7][8][9][10][11] However, predicting factors speci c to CR remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several liver diseases, such as hepatitis virus infection, alcoholism, and nonalcoholic fatty liver disease, are often associated with the development of HCC[ 3 - 5 ]. When diagnosed, more than 80% of patients are in the advanced stage when they are diagnosed and have obvious resistance to conventional chemotherapy and radiotherapy[ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%